Between the Market and Leviathan : Revisiting Hayek in the Age of Political Capitalism - da Silva, Joanderson (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2025)
The Last Liberal Man: Hayek in the Age of Political Capitalism, by Vikash Yadav, offers a compelling reinterpretation of Friedrich Hayek's political thought, highlighting its relevance in confronting the contemporary challenges faced by liberalism. Moving beyond oversimplified and ideological portrayals, Yadav reconstructs Hayek’s core ideas as a response to the rise of political capitalism—a model marked by economic growth under centralized political control, seen in countries like China and Vietnam. Structured to echo The Road to Serfdom, each chapter begins with an epigraph and explores themes such as the decline of laissez-faire, the fusion of socialism and nationalism, and the role of individual liberty. The book defends the rule of law, a minimal income guarantee, and a post-nationalist federalism, while also addressing Hayek's controversial positions on inequality and authoritarianism. Ultimately, Yadav calls for the renewal of liberalism by adapting its principles to the evolving geopolitical and economic landscape of the 21st century.